2006
DOI: 10.1530/eje.1.02190
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate versus other environmental sodium/iodide symporter inhibitors: potential thyroid-related health effects

Abstract: Iodine uptake inhibition and any potential downstream effect by perchlorate are highly dependent on the presence of other environmental NIS inhibitors and iodine intake itself. These potential confounders should therefore be considered in future studies and calculations for risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 45 publications
3
84
1
Order By: Relevance
“…It has received recent Aquaculture 436 (2015) 8-12 attention as an endocrine disrupting chemical (EDC) due to its effect on reproductive and thyroid hormone systems (Edwards and Guillette, 2007;Edwards et al, 2006;Guillette and Edwards, 2005;Hamlin et al, 2008). Nitrate is a goitrogen and interferes with the production of thyroid hormones (THs) by competitively binding to the sodium/iodide symporter (NIS) on thyroid follicles, decreasing the availability of iodide (I − ) for use in TH synthesis (De Groef et al, 2006;Lahti et al, 1985;Tonacchera et al, 2004). Female Wistar rats exposed to NO 3 − in their drinking water for 30 weeks experienced significant reductions in total triiodothyronine (TT 3 ) at doses of 50, 250 and 500 mg/L NO 3 − (Eskiocak et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has received recent Aquaculture 436 (2015) 8-12 attention as an endocrine disrupting chemical (EDC) due to its effect on reproductive and thyroid hormone systems (Edwards and Guillette, 2007;Edwards et al, 2006;Guillette and Edwards, 2005;Hamlin et al, 2008). Nitrate is a goitrogen and interferes with the production of thyroid hormones (THs) by competitively binding to the sodium/iodide symporter (NIS) on thyroid follicles, decreasing the availability of iodide (I − ) for use in TH synthesis (De Groef et al, 2006;Lahti et al, 1985;Tonacchera et al, 2004). Female Wistar rats exposed to NO 3 − in their drinking water for 30 weeks experienced significant reductions in total triiodothyronine (TT 3 ) at doses of 50, 250 and 500 mg/L NO 3 − (Eskiocak et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In previous epidemiological studies, nitrate intake was considered as a potential cancer risk factor due to contamination of drinking water. [36][37][38] Regarding thyroid function, nitrate can competitively inhibit iodide uptake, 39,40) which may cause a reduction in thyroid hormone production. 41) In an assessment of the Iowa Women's Health Study, high nitrate intake through drinking water consumption and private well use seemed to increase the risk of ovarian cancer in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the stomach, nitrite reacts with amines, amides, or amino acids and produces N-nitroso compounds, very important carcinogens for animals (Mirvish 1995). Nitrate, in turn, competes with iodine and may inhibit iodine uptake, affecting thyroid hormone production, which might lead to a stimulation of thyroid growth and tumor formation (Tonacchera et al 2004, De Groef et al 2006. Other authors have suggested that dairy protein may increase circulating concentrations of insulin-like growth factor 1 (IGF1; Crowe et al 2009).…”
Section: Systemic Changesmentioning
confidence: 99%